2018
DOI: 10.5815/ijitcs.2018.04.06
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis and Proposing ‘ANN Fuzzy AHP Model’ for Requirements Prioritization

Abstract: Abstract-Requirements prioritization is an essential component of software release planning and requirement engineering. In requirement engineering the requirements are arranged as per their priority using prioritization techniques to develop high-quality software's. It also helps to the decision makers for making good decisions about, which set of requirements should be executed first. In any software development industry a 'software project' may have a larger number of requirements and then it is very diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…• [108] • [72] proposed a method, which is a combination of point direct scoring (PDS) and AHP and Kano model. After evaluation with the help of the Kano model, It is found that newly proposed approach namely "T4" can help for obtaining a higher accuracy rate.…”
Section: Requirements Prioritization Approaches Based On Ahpmentioning
confidence: 99%
“…• [108] • [72] proposed a method, which is a combination of point direct scoring (PDS) and AHP and Kano model. After evaluation with the help of the Kano model, It is found that newly proposed approach namely "T4" can help for obtaining a higher accuracy rate.…”
Section: Requirements Prioritization Approaches Based On Ahpmentioning
confidence: 99%
“…Fuzzy sets have found application in enhancing classical prioritization techniques, notably in the Fuzzy Analytic Hierarchy Process (AHP). In the Fuzzy AHP, pairwise comparisons of candidate features and hierarchical criteria are conducted using linguistic terms expressed in triangular or trapezoidal functions, deviating from traditional numerical values [45]. Recognizing the scalability challenges associated with AHP and similar techniques, especially in extensive software projects where stakeholders need to evaluate numerous features, we introduced a Recommender System (RS) within the context of features prioritization.…”
Section: Fuzzy Sets-based Methods In Software Requirements/features P...mentioning
confidence: 99%
“…Fuzzy AHP [20] is another approach introduced to solve the scalability issue that faces AHP [11]. The main idea of Fuzzy AHP is to use fuzzy scales [21], and the pairwise comparison matrix consists of fuzzy triangle numbers. It provides flexibility and efficiency to get benefits from the decision-maker's preferences.…”
Section: Related Workmentioning
confidence: 99%
“…Fuzzy AHP ANN [21] is an artificial intelligence decision support system proposed to deal with large requirements numbers [18]. It integrates the Artificial intelligence Neural Network (ANN) with AHP to select the best alternatives.…”
Section: Related Workmentioning
confidence: 99%